Laser-driven high-strain-rate micro-nano impact indentation testing method

CN119334796AActive Publication Date: 2025-01-21JILIN UNIVERSITY

Patent Information

Application Number
CN202411525987.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-21
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

电磁/压电驱动的微纳米冲击压痕测试方法,尽管具有高通量、安全、微尺度等优势,然而,其应变率往往也小于103s-1,且需要配合精度和采样频率较高的传感及采集设备并与复杂的数据后处理程序配合才能完成测试

Benefits of technology

[0020]激光驱动高应变率微纳米冲击压痕测试方法,本发明的有益效果在于:通过综合激光冲击以及弹性变形机理,获得了一种微观尺度下,应变率高、安全以及高效的微纳米冲击压痕测试方法,有效解决了如霍普金森压杆、摆锤及弹道冲击等常规测试方法面临的测试尺度为宏观测试、应变率低、测试通量低以及安全系数低等问题,为高应变率冲击载荷作用下材料微观变形与损伤机制研究提供了新的方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119334796A_ABST
    Figure CN119334796A_ABST
Patent Text Reader

Abstract

The invention relates to a laser-driven high-strain-rate micro-nano impact indentation testing method, and belongs to the field of precision testing. The method comprises the following steps: (1) determining a laser shock position on the surface of an elastomer, and laying an absorption layer at a corresponding position; (2) a transparent restraint layer is laid on the surface of the absorption layer, and an impact component composed of a pressing head, an elastic body, the absorption layer and the restraint layer is constructed; (3) adjusting the position of an impact part to be positioned on a laser focus plane, and simultaneously ensuring that a laser spot, a pressure head and a to-be-impacted area of the sample are coaxial; (4) adjusting the position of the sample to enable the distance between the sample and the tip of the pressure head to be 0-1mm; and (5) adjusting parameters of the laser device and the high-speed camera, synchronously starting the laser device and the high-speed camera, carrying out laser-driven high-strain-rate micro-nano impact indentation test, shooting indentation and ejection processes of the indenter in real time, and measuring speed characteristics. The method is realized by integrating laser shock and an elastic deformation mechanism, and has a relatively high strain rate for testing under a micro scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of precision testing, and in particular to a testing method for achieving high strain rate micro-nano impact indentation by generating laser-induced plasma and driving the deformation of an elastic body to drive an indenter to impact a material. Compared with conventional impact testing methods such as Hopkinson bar and pendulum impact, this method is an impact test at a microscopic scale, and has the advantages of high flux, high strain rate, and high safety factor. Background Art

[0002] High strain rate and high-speed impact often lead to rapid changes in parameters such as temperature and stress inside the material. In the fields of space-to-earth hypersonic vehicles, aero engines, gas turbines, nuclear power equipment, etc., the core components of the equipment are often subjected to high-speed impact, which has become one of the important causes of weakening or even failure of key components of the equipment. Therefore, studying and revealing the microscopic deformation and damage mechanism of materials under high strain rate impact loads is a prerequisite for optimizing material design, improving material performance, and ensuring equipment safety, and it is also a cutting-edge scientific problem that needs to be solved urgently in the field.

[0003] Compared with the mechanical property test of materials under quasi-static conditions, the parameters obtained under high-speed impact conditions are more capable of describing the performance of materials under actual working conditions. Unfortunately, although several impact test methods have been developed, they have different limitations in terms of strain rate upper limit, test scale, test flux and safety. Methods such as Hopkinson pressure bar, laser-driven flying sheet technology, pendulum impact and ballistic impact are usually carried out on macro-scale samples (several millimeters to hundreds of millimeters), requiring higher impact speeds (hundreds of meters per second) to produce larger strain rates. In the test results provided by the above methods, the strain rate is generally between 10 4 s -1 The electromagnetic / piezoelectric driven micro-nano impact indentation test method has the advantages of high throughput, safety, and micro-scale. However, its strain rate is often less than 10 3 s -1 , and it needs to cooperate with sensors and acquisition equipment with high precision and sampling frequency and complex data post-processing programs to complete the test. Laser shock is a fast and direct energy transfer method that can transfer a large amount of energy in a local area. It has been widely used in the fields of metal processing and surface strengthening. The test method proposed in the present invention combines laser shock and elastic deformation mechanisms, effectively solving the problems of low strain rate and macroscopic test scale faced by conventional test methods, and provides a new method for studying the microscopic deformation and damage mechanism of materials under high strain rate impact loads. Summary of the invention

[0004] The purpose of the present invention is to provide a laser-driven high strain rate micro-nano impact indentation test method, which solves the problems existing in the prior art. The present invention generates plasma by laser induction and drives the elastic body to deform and drive the indenter to impact the material to achieve high strain rate micro-nano impact indentation test.

[0005] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0006] The laser-driven high strain rate micro-nano impact indentation test method includes the following steps:

[0007] (1) Determine the laser impact position on the elastomer surface and lay an absorption layer at the corresponding position;

[0008] (2) placing a transparent constraining layer on the surface of the absorbing layer to construct an impact component consisting of a pressure head, an elastic body, an absorbing layer, and a constraining layer;

[0009] (3) adjusting the impact component position so that it is located in the laser focal plane and making the laser spot, the indenter and the sample to be impacted coaxial;

[0010] (4) Adjust the sample position so that the distance between the sample and the tip of the indenter is 0 to 1 mm;

[0011] (5) Adjust the laser and high-speed camera parameters, start the laser and high-speed camera synchronously, and perform laser-driven high-strain rate micro-nano impact indentation testing. At the same time, the indenter indentation and ejection process are captured in real time and the speed characteristics are measured.

[0012] The laser ablates the absorption layer and generates high-temperature, high-pressure plasma. The expansion of the plasma is constrained by the constraint layer and the elastomer, so that the high-intensity shock wave is transmitted to the elastomer and then impacts the elastomer to cause elastic deformation of the elastomer. The conversion of elastic potential energy into kinetic energy drives the indenter to impact the test material, thereby completing the high strain rate impact indentation test.

[0013] The indenter in step (2) includes a standard Bosch diamond indenter, a standard Vickers diamond indenter and cylindrical diamond indenters of different diameters. The indenter consists of a diamond tip and a base. The base has a diameter of 0 to 5 mm, a height of 1 to 2 mm and a weight of 0.001 to 0.2 g.

[0014] In the step (2), the elastic material is a metal spring.

[0015] The constrained layer in step (2) is a transparent acrylic plate with a thickness of 1 to 10 mm or BK-7 glass with high impact resistance.

[0016] The pressing and ejecting process in step (5) includes plasma generation, elastic deformation of the elastic body, pressing and ejecting of the indenter. The measured speed includes elastic deformation speed, indenter impact speed and rebound speed.

[0017] The connection between the pressure head and the elastic body includes bonding with a special metal adhesive, welding and mechanical connection.

[0018] The absorption layer has a thickness in the range of 50 to 200 μm.

[0019] The laser-driven high strain rate micro-nano impact indentation test method can achieve a strain rate range of 10 3 -10 6 s -1 .

[0020] The laser-driven high strain rate micro-nano impact indentation testing method has the beneficial effect of: by integrating laser impact and elastic deformation mechanism, a micro-nano impact indentation testing method with high strain rate, safety and efficiency at micro scale is obtained, which effectively solves the problems faced by conventional testing methods such as Hopkinson pressure bar, pendulum and ballistic impact, such as macroscopic testing scale, low strain rate, low test flux and low safety factor, and provides a new method for the study of microscopic deformation and damage mechanism of materials under high strain rate impact load. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings described herein are used to provide further understanding of the present invention and constitute a part of this application. The illustrative examples of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1 Schematic diagram of laser-driven high strain rate micro-nano impact indentation test;

[0023] Figure 2 The strain rate when the laser energy is 1400mJ and the glassy alloy is impacted by a Bosch indenter;

[0024] Figure 3 The residual morphology and cross-sectional profile curve of the sample surface after the laser energy is 1400mJ and the amorphous alloy is impacted by a Bosch indenter;

[0025] Figure 4 The residual surface morphology and cross-sectional profile curve of the sample after the laser energy is 1400mJ and the 1050 aluminum alloy is impacted by a Brinell indenter.

[0026] Figure 5 The residual morphology of the sample surface after shot peening of high entropy alloy using a Bosch indenter with a laser energy of 1400mJ.

[0027] In the figure, 101 is a test sample; 102 is an elastomer before and after deformation; 103 is a laser energy absorption layer; 104 is a BK-7 glass or acrylic plate with high impact impedance; 105 is a diamond indenter; 106 is a laser; 107 is a high-speed camera; 108 is a diamond tip of the indenter; and 109 is a base of the indenter. DETAILED DESCRIPTION

[0028] The following further describes the details of the present invention and its specific implementation methods in conjunction with the accompanying drawings. Figures 1 to 5 As shown, the laser-driven high strain rate micro-nano indentation impact testing method of the present invention comprises the following steps:

[0029] (1) Determine the laser impact position on the elastomer surface and lay an absorption layer at the corresponding position;

[0030] (2) placing a transparent constraining layer on the surface of the absorbing layer to construct an impact component consisting of a pressure head, an elastic body, an absorbing layer, and a constraining layer;

[0031] (3) adjusting the impact component position so that it is located in the laser focal plane and making the laser spot, the indenter and the sample to be impacted coaxial;

[0032] (4) Adjust the sample position so that the distance between the sample and the tip of the indenter is 0 to 1 mm;

[0033] (5) Adjust the laser and high-speed camera parameters, start the laser and high-speed camera synchronously, and perform laser-driven high-strain rate micro-nano impact indentation testing. At the same time, the indenter indentation and ejection process are captured in real time and the speed characteristics are measured.

[0034] The laser ablates the absorption layer and generates high-temperature, high-pressure plasma. The expansion of the plasma is constrained by the constraint layer and the elastomer, so that the high-intensity shock wave is transmitted to the elastomer and then impacts the elastomer to cause elastic deformation of the elastomer. The conversion of elastic potential energy into kinetic energy drives the indenter to impact the test material, thereby completing the high strain rate impact indentation test.

[0035] The indenter in step (2) includes a standard Bosch diamond indenter, a standard Vickers diamond indenter and cylindrical diamond indenters of different diameters. The indenter consists of a diamond tip and a base. The base has a diameter of 0 to 5 mm, a height of 1 to 2 mm and a weight of 0.001 to 0.2 g.

[0036] In the step (2), the elastic material is a metal spring.

[0037] The constrained layer in step (2) is a transparent acrylic plate with a thickness of 1 to 10 mm or BK-7 glass with high impact resistance.

[0038] The pressing and ejecting process in step (5) includes plasma generation, elastic deformation of the elastic body, pressing and ejecting of the indenter. The measured speed includes elastic deformation speed, indenter impact speed and rebound speed.

[0039] The connection between the pressure head and the elastic body includes bonding with a special metal adhesive, welding and mechanical connection.

[0040] The absorption layer has a thickness in the range of 50 to 200 μm.

[0041] The laser-driven high strain rate micro-nano impact indentation test method can achieve a strain rate range of 10 3 -10 6 s -1 .

[0042] Example:

[0043] See also Figure 1 The figure shows a schematic diagram of laser-driven high strain rate micro-nano impact indentation test. First, determine the laser impact position on the surface of the elastomer, and lay an absorption layer at the corresponding position. The absorption layer is a black double-sided adhesive with double-sided stickiness and a thickness of 90 microns; lay a transparent constraint layer on the surface of the absorption layer, and construct an impact component consisting of a diamond indenter, an elastomer, an absorption layer, and a constraint layer; adjust the impact component position so that it is located in the laser focal plane and make the laser spot, the indenter, and the sample to be impacted coaxial; adjust the sample position so that the distance between the sample and the indenter tip is 0 to 1 mm; adjust the laser and high-speed camera parameters, start the laser and high-speed camera synchronously, and perform a laser-driven high strain rate micro-nano impact indentation test, while taking real-time photos of the indenter pressing and ejection process and measuring the speed characteristics. The mechanism of the present invention is as follows: a laser (106) ablates an absorption layer (103) and generates high-temperature, high-pressure plasma; the expansion of the plasma is constrained by a constrained layer (104) and an elastic body (102), so that a high-intensity shock wave is transmitted to the elastic body (102), and then impacts the elastic body (102), causing the elastic body (102) to produce elastic deformation; and the conversion of elastic potential energy into kinetic energy drives the indenter (105) to impact the test material (101), thereby completing a high strain rate impact indentation test.

[0044] See also Figure 2 As shown in the figure, when the laser energy is 1400mJ, the strain rate is when the glassy alloy is impacted by the Bosch indenter. It can be seen that the strain rate level is 10 5 s -1 >10 4 s -1 ,Compared with the conventional impact testing method, the strain rate obtained by this ,method is increased by one order of magnitude.

[0045] See also Figure 3 , Figure 4 and Figure 5 The figure shows the residual morphology of the sample surface obtained after laser-driven micro-nano impact indentation test on amorphous alloy, 1050 aluminum alloy and high entropy alloy after spray strengthening with a laser energy of 1400mJ using a Bosch or Burkina Fasci indenter. It can be seen that the residual morphology of the sample under quasi-static indentation test is significantly different.

[0046] It can be seen from the example results that the laser-driven high strain rate micro-nano impact indentation test method proposed in the present invention combines laser impact and elastic deformation mechanisms to effectively solve the problems of low strain rate and macroscopic test scale faced by conventional testing methods, and provides a new method for the study of microscopic deformation and damage mechanism of materials under high strain rate impact loads.

[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made to the present invention shall be included in the protection scope of the present invention.

Claims

1. A laser-driven high strain rate micro-nano impact indentation test method, characterized in that: The following steps are involved: (1) Determine the laser impact position on the elastomer surface and lay an absorption layer at the corresponding position; (2) placing a transparent constraining layer on the surface of the absorbing layer to construct an impact component consisting of a pressure head, an elastic body, an absorbing layer, and a constraining layer; (3) adjusting the impact component position so that it is located in the laser focal plane and making the laser spot, the indenter and the sample to be impacted coaxial; (4) Adjust the sample position so that the distance between the sample and the tip of the indenter is 0 to 1 mm; (5) Adjust the laser and high-speed camera parameters, start the laser and high-speed camera synchronously, perform laser-driven high-strain rate micro-nano impact indentation test, and simultaneously shoot the indenter indentation and ejection process in real time and measure the speed characteristics; The mechanism is as follows: the laser ablates the absorption layer and generates high-temperature, high-pressure plasma. The expansion of the plasma is constrained by the constraint layer and the elastic body, so that the high-intensity shock wave is transmitted to the elastic body and then impacts the elastic body to cause elastic deformation of the elastic body. The conversion of elastic potential energy to kinetic energy drives the indenter to impact the test material, thereby completing the high strain rate impact indentation test. The indenter in step (2) includes a standard Bosch diamond indenter, a standard Vickers diamond indenter, and cylindrical diamond indenters of different diameters, the indenter consisting of a diamond tip and a base, the base having a diameter of 0 to 5 mm, a height of 1 to 2 mm, and a weight of 0.001 to 0.2 g; In the step (2), the elastic material is a metal spring; The constrained layer in step (2) is a transparent acrylic plate with a thickness of 1 to 10 mm or BK-7 glass with high impact resistance; The pressing and ejecting process in step (5) includes plasma generation, elastic deformation of the elastomer, pressing and ejecting of the indenter; and the measured speed includes elastic deformation speed, indenter impact speed and rebound speed.

2. The laser-driven high strain rate micro-nano impact indentation testing method according to claim 1, characterized in that: The connection between the pressure head and the elastic body includes bonding with a metal adhesive, welding and mechanical connection.

3. The laser-driven high strain rate micro-nano impact indentation testing method according to claim 1, characterized in that: The absorption layer has a thickness in the range of 50 to 200 μm.

4. The laser-driven high strain rate micro-nano impact indentation testing method according to claim 1, characterized in that: The strain rate range achieved by this method is 10 3 -10 6 s -1 .

Citation Information

Patent Citations

  • In-situ micro-nano indentation / scratch test platform and test method

    CN104729911A

  • High-strain-rate nanoindentation testing device and method

    CN114705570A

  • Double-scale texture preparation device and method for laser shock imprinting

    CN115846881A

  • Momentum exchange driving type impact indentation testing device and testing method

    CN117007454A

  • Pulse current-assisted laser peen forming and hydrophobic surface preparing method for aluminum alloy

    US11753694B1

Cited By

  • Automobile windshield strength detection device

    CN119666573A